Large costs and small benefits of the American sugar programme. - Maskus, Keith E. (1989)
Discusses the evolution of the sugar policy of the US in the 1980s and its effects on the country's trade and international relations. Concludes that these effects appear to be negative in virtually all respects, and calls for the liberalization of the quotas.